Emergencies and criminal law in Kant’s legal philosophy. - Thomas Mertens (Ethic@: an International Journal for Moral Philosophy)
Despite Kant's explicit statement that every murderer must suffer death, there are at least four situations to be found in Kant's work in which the killing of a human being should not lead to the death penalty: when too many murderers are involved; when a mother kills her illegitimate child; when one duellist kills the other; when one person pushes another off a plank in order to save his life. This paper discusses these situation and concentrates on the last situation - Kant's interpretation of the plank of Carneades – with an eye to what they learn us about Kant understanding of the law. Does Kant acknowledge a legal vacuum? In order to come to a conclusion, Kant's 'solution' of the plank is compared with those suggested by other authors, such as Cicero, Pufendorf and Lon Fuller in his famous 'speluncean explorers' case.